2011
DOI: 10.1111/j.1474-919x.2011.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐equatorial migration, staging sites and wintering area of Sabine’s GullsLarus sabiniin the Atlantic Ocean

Abstract: The migrations and winter distributions of most seabirds, particularly small pelagic species, remain poorly understood despite their potential as indicators of marine ecosystem health. Here we report the use of miniature archival light loggers (geolocators) to track the annual migration of Sabine’s Gull Larus sabini, a small (c. 200 g) Arctic‐breeding larid. We describe their migratory routes and identify previously unknown staging sites in the Atlantic Ocean, as well as their main Atlantic wintering area in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 55 publications
(123 reference statements)
3
65
0
Order By: Relevance
“…Dunn 2002), and seabirds (e.g. Stenhouse et al 2012), including Arctic terns breeding in the Atlantic (Egevang et al 2010). Our behavioral data lend support to the idea that the birds used these stopovers as refueling opportunities, as foraging behavior was more prominent within staging areas than within travel corridors.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Dunn 2002), and seabirds (e.g. Stenhouse et al 2012), including Arctic terns breeding in the Atlantic (Egevang et al 2010). Our behavioral data lend support to the idea that the birds used these stopovers as refueling opportunities, as foraging behavior was more prominent within staging areas than within travel corridors.…”
Section: Discussionsupporting
confidence: 68%
“…We identified staging areas to include any positions where latitudinal movements were < 0.8° over a 12 h period, smoothed over 3 d (Egevang et al 2010, Stenhouse et al 2012. These areas included both migratory stopover regions as well as the colony region and wintering ground.…”
Section: Staging Areas Vs Travel Corridorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The at-sea area used by Bugio petrels during this stage seems to overlap with the distribution of Zino's petrels Pterodroma madeira from Madeira (Zino et al 2011), Cory's shearwater Calonectris diometea from Desertas (Paiva et al 2010a) and Selvagens (Paiva et al 2010c), and Cape Verde shearwater Calonectris edwardsii from Cape Verde (Roscales et al 2011). The African shelf area along the coast of Mauritania appears to be very important for populations of these 4 seabird species for part or all of the year and also for migrant seabirds from elsewhere, including Sabine's gull Larus sabini (Kopp et al 2011), northern gannet Morus bassanus (Stenhouse et al 2012), great skua Stercorarius skua (Magnusdottir et al 2012) and south polar skua S. maccormicki (Fort et al 2012). In fact, this area is within one of the most important large marine ecosystems in the world -the Canary Current -with strong and nutrient-rich upwelling, which naturally elevates primary productivity and progressively increases the abundance of plankton and small planktivorous pelagic fish, cephalopods and crustaceans, which ultimately attracts seabirds to the area (Mann & Lazier 2006, Sherman & Hempel 2009).…”
Section: Habitat Use During the Breeding Stagementioning
confidence: 99%
“…1). Several mid-to-long distance migratory seabirds have been tracked throughout their annual cycle in the Atlantic, and a considerable number amongst them migrate through the offshore tropical Atlantic, but with the exception of Zino's petrel (Zino and Biscoito 2011), none select the areas used by Bulwer's petrels during winter (Ronconi 2007;Guilford et al 2009;Dias et al 2011;Kopp et al 2011;Sittler et al 2011; Stenhouse et al 2012). These tropical midAtlantic areas are mostly known to be of low productivity (Ramírez et al 2013) and have even been suggested to act as an ecological barrier for long distance seabird migrants (Dias et al 2012a).…”
Section: Discussionmentioning
confidence: 99%